Une moissonneuse-batteuse sur la plaine rizicole de Bama (Burkina Faso) : leçons et perspectives d’un service commun de mécanisation agricole - Tewendé Laurent Ouedraogo (EchoGéo)
Agricultural mechanization is an important aspect of Burkina Faso's public agricultural policies, because of the multifaceted challenges that face an agricultural sector that predominates in the economy in terms of the number of people employed (nearly 80%), but which remains very poorly mechanized. On the rice-farming plain of Bama, between 2019 and 2022, a project to develop an agricultural mechanization service was implemented with the introduction of a combine harvester. Its aim is to improve agricultural productivity through the creation of a rice harvesting service, for which a fee is now charged. Experience with this project, at both organizational and operational levels, raises the question of the conditions for implementing agricultural innovations.